Upaya Pengelola Pesantren Lorong Raudhah Indonesia Makassar dalam Meningkatkan Literasi bagi Lanjut Usia - Uswatul Ilmi; Andi Ibrahim; La Ode Ismail Ahmad (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
The main problem discussed in this thesis research is the efforts made by the management of the Jalan Raudhah Indonesia Islamic boarding school in Makassar to increase Islamic literacy for the elderly and the impact of literacy activities carried out at the Jalan Raudhah Indonesia Islamic boarding school in Makassar. The aim of this research is to describe the efforts made by the management of the Indonesian Alley Raudhah Islamic boarding school to increase Islamic literacy for the elderly as well as the impact of literacy activities at the Indonesian Alley Raudhah Islamic boarding school. The type of research used is descriptive research with a managerial and pedagogical approach. Then the data sources in this research are primary data and secondary data..Based on the results of the research, it was concluded that the efforts of the management of the Jalan Raudhah Indonesia Islamic boarding school in Makassar to increase literacy for the elderly were through a process of habituation, learning and development. The impact of literacy activities carried out in the Indonesian Alley Raudhah Islamic boarding school is the ability to read, write and speak spoken language for elderly students.The implication of the literacy activities carried out by the management of the Jalan Raudhah Indonesia Islamic boarding school in Makassar is that elderly students are more informed and can spend their old age with various positive activities and get closer to the Creator, besides that harmony between residents in the Islamic boarding school environment is well established.